(untitled) (Encuentros, 2024)
This scientific article presents the results of an investigation that describes the perceptions of the use of code switching held by English teachers and students of the first, fifth and eighth semesters of the Bachelor’s Degree in Foreign Languages with Emphasis in English at the Universidad Central del Valle. The research had a mixed approach, with a descriptive and interpretive scope and a multiple case study design (Katayama, 2004). The instruments used were an ad hoc questionnaire and a semi-structured interview for teachers and students. The results showed that the use of code switching would be necessary for classroom discourse management, reduce anxiety levels and increase motivation in students.